Age-related plumage differences of Dunlins along the East Asian-Australasian Flyway - Choi, Chiyeung; Hua, Ning; Persson, Christer; Chiang, Chungyu; Ma, Zhijun (Journal of Field Ornithology, 2010)
For some populations of Dunlins (Calidris alpina), determining the age of individuals on the nonbreeding grounds can be difficult. This difficulty arises in part because some populations undergo their primary molt during the boreal summer, leaving adult and first-year Dunlins with similar amounts of abrasion on their primaries. Ageing Dunlins is further complicated by the presence of adults with buff-fringed, inner median coverts in some populations, a feature often used to age juvenile Dunlins. We examined a number of characteristics helpful in the ageing Dunlins at nonbreeding areas along the East Asian-Australasian Flyway, including: (1) the pattern of white fringes on the inner primary coverts, (2) the color of fringes on the inner median wing coverts, (3) the color of the tip on the carpal covert, (4) the presence or absence of a dark subterminal band on tertial or tertial coverts, and (5) remnants of alternate or juvenile plumage on the belly. Our results demonstrate that the pattern of white fringes on the inner primary coverts is an important character for ageing Dunlin along the East Asian-Australasian Flyway. In addition, we found that all characteristics used for ageing fade with time, and that breeding adults along the East Asian-Australasian Flyway are more difficult to age than adults elsewhere, in part due to the presence of " adult buff" coverts (ABCs) and in part because of the early timing of primary molt. Finally, we suggest that the presence of ABCs might be useful for differentiating the two Dunlin subspecies (C. a. arcticola and C. a. pacifica) occurring in Alaska. ©2010 The Author(s). Journal compilation